PELAKSANAAN SOSIALISASI APLIKASI ADA AMARI COVID 19 DI KELURAHAN MELONG TENGAH KOTA CIMAHI JAWA BARAT - Yustikasari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Education is very important in efforts to reduce Covid-19 cases in Indonesia. There are still quite a lot of people who don't care and seem dismissive, it is proven that so far the Covid-19 case has not ended. Some people, apart from not caring, there are also groups of people who care so much that they are afraid to overdo it. This is certainly not good. Padjadaran University with the ADA AMARI Covid-19 Humanitarian Community Service Theme also contributed to dealing with this problem through its students by conducting Real Work Lectures. The Covid 19 problem occurred in various cities in Indonesia, while the locus of focus was in Melong Tengah, Melong Village, Cimahi City. One of the objectives of the KKN implementation is to increase knowledge and skills in managing digital technology (Digital literacy) to improve the health, social and economic status of the community. The method used is training and counseling. The results of the KKN that were carried out were obtained through the AMARI survey as many as 342 data from the total population of Melong Tengah, Cimahi City, which was 27,522 people or around 1.39%.